3(2p+3q)+-4q=

Simple and best practice solution for 3(2p+3q)+-4q= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2p+3q)+-4q= equation:


Simplifying
3(2p + 3q) + -4q = 0
(2p * 3 + 3q * 3) + -4q = 0
(6p + 9q) + -4q = 0

Combine like terms: 9q + -4q = 5q
6p + 5q = 0

Solving
6p + 5q = 0

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-5q' to each side of the equation.
6p + 5q + -5q = 0 + -5q

Combine like terms: 5q + -5q = 0
6p + 0 = 0 + -5q
6p = 0 + -5q
Remove the zero:
6p = -5q

Divide each side by '6'.
p = -0.8333333333q

Simplifying
p = -0.8333333333q

See similar equations:

| -7x-6=-12x-41 | | -n=1/4^-4 | | (x^2-4x-2)(x+7)= | | -n=1/9^-2 | | -14x+6=-6x+38 | | -14x+6=-6+38 | | 3x-2=-4x+33 | | 17x-2=8x+88 | | -n=1/5^-5 | | 9y-1=-10+12y | | -5(7n-4)+3= | | 2y-14=4y+4 | | P=2(26)+2(91) | | 5y+6y-81=7y+102+65 | | 3t^4=8t | | x+x+125000=550000000 | | 12x+8y-12=0 | | 4*x-9/2+12=0 | | 51x^2-5x-4= | | x+x+4=238 | | -(6y+5)-(-5y-7)=-5 | | 14-2x+39x-18x=256-60x-657x | | 13-42/7 | | 7+3p-4=9p+10-5p | | -x/3+58= | | -3b=-12 | | 2b+3(b-2)=4 | | -14n+4=-13n-17 | | -8w^2-8w+19=0 | | 12y=11(y+1) | | 4n+10n=28 | | -7.7x=15.4 |

Equations solver categories